The Mission and Function of παρκλητος in Johannine Literature vis-à-vis Nigerian Pentecostal/Charismatic Beliefs and Teachings on παρκλητος - Uzukwu, G. N. (Neotestamentica, 2019)
The topic of παρκλητος (the Paraclete) in John 14–16 exposes not only the unique nature of Johannine Trinitarian theology, but also a pneumatological Christology. This points to the complex nature of the relationship between Christ and παρκλητος, as well as the mission of παρκλητος when Christ ascends. What primary function of παρκλητος is likened to that of Christ? What implications flow forth from an exegetical and socio-historical study of John 14:16–17, 26 and 1 John 2:1 for twenty-first-century Nigerian Christians? This study has Nigeria as its focal point, because this country is noted for numerous Pentecostal and/or charismatic movements with a variety of doctrinal and cultural claims that have met with resistance and even dismissal from mainstream Christian theologians and churches. Using a socio-historical approach, this article will deal with three issues: (1) the meaning of παρκλητος in its Johannine context; (2) the correlation between the Paraclete texts in John in their socio-historical contexts; and (3) a re-evaluation of some Nigerian Pentecostal and charismatic teachings on the working of παρκλητος in light of the socio-historical context of Johannine literature. © New Testament Society of Southern Africa
Paid
Keywords: Charismatic; Holy Spirit; Johannine; Nigeria; Paraclete; Pentecostal; Pneumatology